2014
DOI: 10.4097/kjae.2014.66.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness about the specialty of anesthesiology and the role of anesthesiologists: a national survey

Abstract: BackgroundThe aims of this national survey were to determine the views of Korean people regarding the specialty of anesthesiology and the role of anesthesiologists and to consider the ways in which individual anesthesiologists and the Korean Society of Anesthesiologists inform the public.MethodsThis off-line national survey was conducted by a professional research organization to obtain exact and reliable data. The questionnaire included structured questions to identify perceptions of the specialty of anesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 8 publications
4
24
4
8
Order By: Relevance
“…While in a study done in Hong Kong, 25% [1] and in Korean study was 18.8% [7]. For the question who estimates and transfuse blood intra-op 5% of patients said anesthetist, which was similar result with the study done by Korean association of anesthesiologists [7]. For the smooth recovery in post-op, 21% of our patients replied anesthetists are responsible while in the study done in Hong Kong it was 65% [1].…”
Section: Knowledge Of Patients About Anesthetist Frequency Percentsupporting
confidence: 69%
See 2 more Smart Citations
“…While in a study done in Hong Kong, 25% [1] and in Korean study was 18.8% [7]. For the question who estimates and transfuse blood intra-op 5% of patients said anesthetist, which was similar result with the study done by Korean association of anesthesiologists [7]. For the smooth recovery in post-op, 21% of our patients replied anesthetists are responsible while in the study done in Hong Kong it was 65% [1].…”
Section: Knowledge Of Patients About Anesthetist Frequency Percentsupporting
confidence: 69%
“…In our study a bit higher value which is 57% of patients taught anesthetists intraoperatively monitor heart, blood pressure and breathing. While in a study done in Hong Kong, 25% [1] and in Korean study was 18.8% [7]. For the question who estimates and transfuse blood intra-op 5% of patients said anesthetist, which was similar result with the study done by Korean association of anesthesiologists [7].…”
Section: Knowledge Of Patients About Anesthetist Frequency Percentsupporting
confidence: 65%
See 1 more Smart Citation
“…Lee ve ark. (10) toplum tarafından sırasıyla televizyon programları, açıklayıcı broşürler ve internetin farkındalığı oluşturmada yeğlendiğini belirten bir çalışma yapmışlardır.…”
Section: Discussionunclassified
“…Anesthesiology is one of medical Science branches (Sable et al, 2016), it has been grown in the recent pastyears (Cooper et al, 1995), by development of monitoring system, new anesthetic agents and techniques (Khara et al, 2013), however it is behind the light, the knowledge about this specialty and the exact role of anesthesiologists is limited between public (Cooper et al, 1995).After the great advances in anesthesia field (Lee et al, 2014), now anesthesiologists play a very important role in peri-operative, the operating room, intensive care, trauma centers,pain management and on the code team (Lee et al, 2014;Prasad et al, 2014; Kadriet al, 2014), however they don't receive the deserved attention andtheir due regards between public (Prasad et al, 2014), this limited awareness of public about the anesthesiologist exceeds anesthesiologist's role in the operating room (Ribeiro et al, 2015), reaching to anesthetist's roles outside the operation room (Garry, 2001). This lack in public awareness about anesthetist's role is not new (Armitage, 1978).Many studies have reported a low public awareness about anesthesia and the role of anesthetists in both developing and developed countries (Swinhoe et al, 1994;Jathar et al, 2002).Patients think that the surgeon is responsible for tasks of anesthesia(Acosta-Martínez et al, 2016),44.5% think so, while only 22% of them know that anesthesiologistswere the providers of anesthesia ISSN: 2320-5407 Int.…”
mentioning
confidence: 99%